Mathematical Literacy Reviewed from Self Regulated Learning on Collaborrative Problem Solving Assisted by Qr Code (Unnes Journal of Mathematics Education Research, 2022)
The purpose of this study is to describe students' literacy skills in terms of Self Regulated Learning in the Collaborative Problem-Solving model assisted by QR Code. This type of research is descriptive research with a qualitative approach. The research subjects for class XI MIPA 2 SMA Bustanul Ulum NU Bumiayu for the 2021/2022 academic year were 36 people. Data was collected by the method of tests, questionnaires, observation, documentation, and interviews. The results of research on students' TLM achievement in terms of Self Regulated Learning on Collaborative Problem Solving with the help of QR Code are very varied. Mathematical literacy in terms of Self Regulated Learning shows that students with high category TLM and high and medium Self Regulated Learning categories can understand and master the seven basic stages of mathematical literacy, but stage 1 can be completed with additional time. Students with medium category TLM and high and medium categories of Self Regulated Learning can understand and master the three basic stages of mathematical literacy, and students with low category TLM and high and medium categories of Self Regulated Learning can understand and master one stage of basic mathematical literacy.